Exome sequencing in children of women with skewed X-inactivation identifies atypical cases and complex phenotypes. (May 2017) - Giorgio, Elisa; Brussino, Alessandro; Biamino, Elisa; Belligni, Elga Fabia; Bruselles, Alessandro; Ciolfi, Andrea; Caputo, Viviana; Pizzi, Simone; Calcia, Alessandro; Di Gregorio, Eleonora; Cavalieri, Simona; Mancini, Cecilia; et al.
Abstract: Background: More than 100 X-linked intellectual disability (X-LID) genes have been identified to be involved in 10–15% of intellectual disability (ID). Method: To identify novel possible candidates, we selected 18 families with a male proband affected by isolated or syndromic ID. Pedigree and/or clinical presentation suggested an X-LID disorder. After exclusion of known genetic diseases, we identified seven cases whose mother showed a skewed X-inactivation (>80%) that underwent whole exome sequencing (WES, 50X average depth). Results: WES allowed to solve the genetic basis in four cases, two of which (Coffin-Lowry syndrome, RPS6K3 gene; ATRX syndrome, ATRX gene) had been missed by previous clinical/genetics tests. One further ATRX case showed a complex phenotype including pontocerebellar atrophy (PCA), possibly associated to an unidentified PCA gene mutation. In a case with suspected Lujan-Fryns syndrome, a c.649C>T (p.Pro217Ser) MECP2 missense change was identified, likely explaining the neurological impairment, but not the marfanoid features, which were possibly associated to the p.Thr1020Ala variant in fibrillin 1. Finally, a c.707T>G variant (p.Phe236Cys) in the DMD gene was identified in a patient retrospectively recognized to be affected by Becker muscular dystrophy (BMD, OMIM 300376). Conclusion: Overall, our data show that WES may give hints to solve complex ID phenotypes with a likely X-linked transmission, and that a significant proportion of these orphan conditions might result from concomitant mutations affecting different clinically associated genes. Highlights: Whole exome sequencing (WES) solved 4/7 cases with X-linked intellectual disability. Mutations identified by WES not always explained completely probands' phenotypes. Unbiased strategies (whole genome sequencing) are necessary to solve complex cases.